Managing Woodland Caribou in West-Central British Columbia - Cichowski, Deborah B. (Rangifer, 1996)
Initial long term planning for logging on the Tweedsmuir-Entiako caribou winter range began in the early 1980s. Because little information was available on which to base winter range management, the British Columbia Fish and Wildlife Branch began studies on radio-collared caribou in 1983, and an intensive study on caribou winter habitat requirements was conducted from 1985 to 1988. Terrestrial lichens were identified as the primary winter food source for the caribou, and in 1987, caribou winter range ecosystem maps, which emphasized abundance of terrestrial lichens, were produced. The ecosystem maps and information from the caribou study, including potential direct and indirect effects of timber harvesting on the caribou population, were used to develop a management strategy for the winter range. The management strategy comprised two levels of management: a landscape level (Caribou Management Zones); and a site-specific level (caribou habitat/timber values). Timber information associated with BC Ministry of Forests forest cover maps was integrated using a Geographic Information System. Six winter range management options were proposed ranging from harvesting low value caribou habitats only throughout the winter range to total protection of the entire winter range. Impacts of those options on both the caribou population and on the timber supply were evaluated. The options were reviewed through a public planning process, the Entiako Local Resource Use Plan, and recommendations from that process were forwarded to the British Columbia Protected Areas Strategy.